2020
DOI: 10.1016/j.bioorg.2020.104327
|View full text |Cite
|
Sign up to set email alerts
|

Copper (II)-based halogen-substituted chromone antitumor drug entities: Studying biomolecular interactions with ct-DNA mediated by sigma hole formation and cytotoxicity activity

Abstract: Copper-based antitumor drug entities 1-3 derived from substituted (F -, Br -, -CH 3 ) 3formylchromone pharmacophore were synthesized and thoroughly characterized by spectroscopic and single X-ray crystallographic studies. These complexes show structural novelty due to presence of the X-bonds in chromone scaffold which could facilitate higher propensity for nucleic acids via sigma σ-hole interactions. Therefore, structure-activity relationship of 1-3 was studied by performing ct-DNA binding, pBR322 cleavage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Synthesis of complex 1. Experimental information such as FT-IR, 1 H and 13 C NMR, Hirshfeld surface and fingerprint plots.…”
Section: Supporting Information Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Synthesis of complex 1. Experimental information such as FT-IR, 1 H and 13 C NMR, Hirshfeld surface and fingerprint plots.…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…[6,7] Moreover, chromone-based metallodrugs are known to inhibit various types of cancer targets viz., DNA, tRNAs, kinase inhibitor enzymes and topoisomerases. [8][9][10] Zn(II) in chromone-appended ligand framework can be explored as an antitumor agent due to its capability to mediate cleavage of the phosphate diester backbone, redox inertness, Lewis acidity, and rapid ligand exchange. [11] Chelation of Zn(II) to naturally occurring chromone improves the complex's planar functionality thereby, allowing the complex to insert and stack between base pairs of double-helical DNA more readily than the free ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 In this approach, biologically active pharmacophore fragments are tethered with a metal centre to enhance their biological activity. 19,20 Martı ´nez et al reported that upon coordination to an organo-ruthenium fragment, the activity of clotrimazole, an antifungal drug, increased by a factor of 110. 21 Biot et al conjugated a ferrocenyl derivative to chloroquine and demonstrated activity in the case of chloroquine-resistant P. falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…As for copper [19][20][21]24,25] it is a bio-element necessity for the human body that occurs in calcium and phosphorus metabolism. It exhibits two different ionic oxidation states (Cu (II) or Cu (I)) [26], and copper-containing complexes have been identified as the best candidates for anticancer agents [27][28][29][30][31]. The mechanism underlying the anti-tumor activity of these Cu-based complexes is the increase of ROS production and oxidative stress which causes DNA damage, increased death receptor expression and ultimately apoptosis-mediated cell death.…”
Section: Introductionmentioning
confidence: 99%